The Frontier Mythology in the Contemporary U.S. SF at the Core of Literature and Movies - Криницька, Наталія Ігорівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The paper is about studying the role of the frontier mythology in contemporary American science fiction at the core of literature and cinema. The forming of the frontier mythology in the United States is reviewed; the main features of the frontier myth are defined; the genesis, characteristics and development of the space opera as the genre of literature and cinema, which continues the tradition of the American frontier past, are considered; a brief comparative analysis of modern SF works that inherit and/or rethink the frontier tradition is made.